The production process of the game: production phases - Manrubia Pereira, Ana Mª (Historia y Comunicación Social, 2014)
The game as one of the emerging cultural industries in its design is characterized by the confluence of two major areas of creation, audiovisual and computer. Its peculiarities as product cause the traffic by specific determinants and production phases necessary.
Keywords: Game design; audiovisual production; computer resources; cultural industry